Impact of the Renewable Energy Development in Lithuania‘s Energy Economy - Bužinskienė, Rita (European Journal of Sustainable Development, 2019)
Paper is characterized by scientific novelty as it involves a very scarce research problem in Lithuanian‘s energy sector, assessing the impact of renewable energy resources on the energy economy. Renewable energy sources have a multiplier effect in spurring the economy and the development of not only the energy sector but also all the supporting activities related to such industry. The impact of the development of renewable energy is one of the factors that develop the quality of technology innovation development. This study includes the impact of renewable energy on the energy economy, using multiple linear regression models. The results of the study have shown that renewable energy resources: wind, sun, water, geothermal and biomass can not always be used together because they compete with each other and therefore reduce the efficiency of the energy economy. In this context, three combinations of renewable energy resources have been developed, which have been adapted to assess the impact of the energy economy on energy productivity and energy intensity. It has been found that the combination of resources of the second model (M2) RE is significant for the efficiency of the energy economy. Keywords: Renewable energy resources; Energy economy; Impact of efficiency